Evaluation of Passive Fire Protection System on Housing Environment (A Case Study: Perumnas Helvetia Medan) - N. Vinky Rahman; Tika Oktaviani (International Journal of Architecture and Urbanism, 2018)
Nowadays, housing development wide-spreads in various cities in Indonesia. This is due to the increasing needs of the community towards a safe residence with its complete facilities and infrastructure to support the needs of daily life. Housing is not only build and construct, but it should also have a protection effort to make residential shelter safe from disaster, such as fire. Fires in housing have a high level of risk and danger since it can cause material loss and loss of life. Fire passive protection system is an effort to overcome the fire. The use of passive fire protection system is to facilitate the community and firefighters in extinguishing the fire so that the spread of fire does not propagate to other buildings. The purpose of this study is to evaluate the reliability level of passive fire protection system in the housing environment by doing a case study at Perumnas Helvetia Medan. Then, it was done by giving layout design recommendation of the residential area by passive fire protection system theory of building and environment.